The Characteristics of Organic Waste in Hotel Aston Kartika Grogol - Jocelin, Yolanda Thasya; Purwaningrum, Pramiati; Minarti, Astari (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2024)
A hotel is a property that provides temporary accommodation, food and beverage services to guests with a variety of other facilities. Waste generation from hotels is a equal by organic and inorganic waste, of course efforts are needed to deal with this problem. The purpose of this study was to analyze the composition of organic waste in the form of food loss and food waste and to plan a hotel organic waste. Using 2 variables, namely the composition of the type of organic waste. The composition of the waste used was food loss and food waste. The results of the comparison of composting results with SNI 7763:2018 show that the water content exceeds the quality standard. The conclusion of this research is a 50% organic waste with a recycling potential of 100%. The composition of organic waste at Aston Kartika Grogol Hotel in the form of food loss comes from restaurants, kitchens, and meeting rooms that are put together in kitchen trash bags as much as 13%. For food waste, Aston Kartika Grogol Hotel comes from the rooms, public areas, restaurants, kitchens, and there is waste from meeting rooms which are combined into kitchen waste bags as much as 36% of the total hotel waste.